Isimi Taiwo’s Revelation of Gender a Paradigm through drawing - Olarinde, Oladesu Johnson; Otu, John (NIU Journal of Humanities, 2020)
The role artists play in a society is dependent on how much attention he pays to the issues that affect and impact of the people. It is important to add that the mode of depiction in the visual arts also stands as a veritable portal that can make or mare the communication path. Taiwo Isimi relies on the representational art form of hyper realism, and is able appeal to a client’s sensibility that exhibits a paradigm change that favour the female gender in a patriarchal society like Nigeria. Keywords: Paradigm, female, male, girl, society, hyper realism